Patient’s Expectation of Orthodontic Treatment at a Tertiary Health Facility in Lagos, Nigeria - Afolabi, Oyapero; Ogunbanjo, Ogunbiyi B; Adegbite, Kikelomo O; Ajisafe, Olawande A (Orthodontic Journal of Nepal, 2016)
Introduction: An understanding of the expectations and attitude of patients is a prerequisite for appropriate behavioural and clinical management. Objective: To assess patients’ expectations of orthodontic treatment and relationship of gender to this expectation among Nigerian patients. Materials & Method: The descriptive study comprised of patients attending the orthodontic clinic at Lagos State University Teaching Hospital (LASUTH), Nigeria for the first time. A structured questionnaire was used to obtain the socio-demographic information and responses to questions on their expectation of orthodontic treatment. Result: Majority of the respondents had higher expectations on aesthetic outcome of orthodontic treatment than the functional outcomes. They expected to have better smile, teeth straightened and have confidence socially. The lowest mean scores were obtained in the domains of improvement in career and making speech easier. Females had significant higher scores than male participants in all domains explored with the mean highest score in the domain of better smiles; while the highest male mean score was in the domain of straightened teeth. Conclusion: Orthodontics relies heavily on patient cooperation for a successful end result. It is recommended that the orthodontist agrees with the patient on realistic expected treatment outcomes before the treatment commences so that they are not disappointed with the final appearance. Orthodontic Journal of Nepal, Vol. 6 No. 1, June 2016, pp.12-17